MENINGKATKAN KEMAMPUAN MEMBACA AL-QUR’ AN DENGAN MENGGUNAKAN MEDIA KARTU HURUF IQRO’ SISWA KELAS 1 SDN PLALANGAN 03 KALISAT TAHUN PELAJARAN 2016/2017: SDN PLALANGAN 03 KALISAT - MUHIMMAH HALIYAH (Dewan Pendidikan Bondowoso, 2021)
Learning to read the Qur'an must be conducted from an early childhood age so that children are well kown with the life guidelines, but Now as digital technology effect children have begun difficult to read the Qur'an. So that children are not able to read the Qur’an well and fluently. The problems which occurs because many students have difficulty reading hijaiyah well. Teachers and researchers found various problems that occurred in grade I SD from early observation. The research of increasing the Qur'an reading skill using the Iqra card media is an classroom action research which is commonly called CAR. the research implementation have held for 6 months starting from January to June 2017 while.The subjects were students of first grade SDN Plalangan 03 Kalisat Jember which was sum 27 students, consisting of 10 female students, and 17 male students. The object is the using the Iqra cards media to increase Qur’an reading skill. It was consisted of two cycles and each cycle included 4 stages, planning, action, observation and reflection. The first cycle reflection was used as a standard reference for conducting the the second cycle, so that there were improvements from the previous cycle. The findings research concluded that the students skill using the Iqro Card media was effective. It can be seen in the data observation activities carried out by researchers, the average achievement of the first cycle was 66.67%, and the average achievement of the second cyclewas 73.33%. Student activities run smoothly and very well, with an average achievement of first Cycle was 73.18 and the average achievement second cycle was 78.52. The formative test result , first cycle achievement average was 66.48. While the second cycle increased as 73.15. Based explanation above, indicating it was said that the research has been completed as determined by the Elementary School, which is an average of 70.00%. From these data, class action through the using Iqro Card media to increase the g first students Qur’an reading skill at SDN Plalangan 03 Kalisat was successful and achieved the learning objectives which had been set.